Pengaruh KIE dan Dukungan Suami Terhadap Pencegahan Postpartum Blues pada Ibu Nifas - Eka Putri Febriyanti; Ryzky Diah Anggraini (Jurnal Kesehatan Komunitas, 2026)
If left untreated, postpartum blues can lead to depression in the first two weeks after delivery. In Indonesia, postpartum blues is still common, and family-based prevention efforts are still incomplete. This study examines how Communication, Information, and Education (IEC) and partner support can reduce postpartum blues in postpartum women. This study used a quantitative pretest-posttest design with a control group. The sample consisted of 30 postpartum women in the intervention and control groups. The intervention group received IEC and husband support, while the control group received standard care. This study was conducted at PMB Puji Handayani, Sungai Kunjang District, Samarinda City, East Kalimantan Province. Measurements were conducted using the Edinburgh Postnatal Depression Scale (EPDS) questionnaire. The results showed a greater reduction in postpartum blues scores in the intervention group. IEC accompanied by husband support is effective in reducing postpartum blues symptoms. Emotional, instrumental (housework/baby care assistance), and informational support from partners increase maternal coping capacity, reduce care stress, and accelerate psychological recovery. It is recommended that this be implemented in obstetric services.